LED session prior incremental step test enhance VO2max in running - Mezzaroba, Paulo V.; Pessôa Filho, Dalton M. [UNESP]; Zagatto, Alessandro M. [UNESP]; Machado, Fabiana Andrade (Springer Nature, 2018)
This study aimed to investigate the effect of prior LED sessions on the responses of cardiorespiratory parameters during the running incremental step test. Twenty-six healthy, physically active, young men, aged between 20 and 30 years, took part in this study. Participants performed two incremental load tests after placebo (PLA) and light-emitting diode application (LED), and had their gas exchange, heart rate (HR), blood lactate, and rating of perceived exertion (RPE) monitored during all tests. The PLA and LED conditions were compared using the dependent Student t test with significance set at 5%. The T test showed higher maximum oxygen uptake (VO2max) (PLA = 47.2 ± 5.7; LED = 48.0 ± 5.4 ml kg−1 min−1, trivial effect size), peak velocity (Vpeak) (PLA = 13.4 ± 1.2; LED = 13.6 ± 1.2 km h−1, trivial effect size), and lower maximum HR (PLA = 195.3 ± 3.4; LED = 193.3 ± 3.9 b min−1, moderate effect size) for LED compared to PLA conditions. Furthermore, submaximal values of HR and RPE were lower, and submaximal VO2 values were higher when LED sessions prior to the incremental step test were applied. A positive response of the previous LED application in the blood lactate disappearance was also demonstrated, especially 13 and 15 min after the test. It is concluded that LED sessions prior to exercise modify cardiorespiratory response by affecting running tolerance during the incremental step test, metabolite clearance, and RPE. Therefore, LED could be used as a prior exercise strategy to modulate oxidative response acutely in targeted muscle and enhance exercise tolerance.
Keywords: Aerobic metabolism; Blood lactate; Cardiorespiratory; Ergogenic; Phototherapy